The negative effects of the Internet on intellectual security - Al Kabeer, Saadia Ali (Journal of Humanities & Social Sciences, 2017)
This study aimed to investigate the relationship between intellectual security and the Internet, as well as the negative impacts of the internet on the intellectual security among sample of students of Al-Majmaa University. The study proposed that there is statistically relevant relation between the negative impacts of the Internet and the intellectual security. The study responds to the main questions that is represented in what are the negative impacts of the Internet on the intellectual security among a sample of the students of Al-Majmaa University? And from this question there are many sub-questions. The study used the descriptive and analytical approach. A questionnaire was used to collect the data of the study as well as achieving its objectives and hypotheses. The most important findings of the study which were arrived from (51) respondents of the teaching staff in Al-Majmaa University were represented in the fact that the average level of the negative impacts of the Internet on the intellectual security was relatively high among the students and the teaching staff in Al-Majmaa University, and that there is statistically relevant relation between the negative impacts of the Internet and intellectual security.